Availability and adaption of exercise programs in pediatric oncology during the COVID-19 pandemic and beyond: a nationwide follow-up survey of providers in Germany - Kesting, Sabine; Gaser, Dominik; Queisser, Jennifer; Götte, Miriam; von Luettichau, Irene; Peters, Christiane; Oberhoffer-Fritz, Renate; Gauß, Gabriele (Frontiers in Pediatrics, 2024)
The COVID-19 pandemic has presented major challenges to clinical practice and delivery of care programs throughout all health care systems. Exercise programs, that are implemented in most centers for pediatric oncology in Germany, are a relatively new care program however with high clinical impact and health benefits. Objective: The impact and consequences of the pandemic on the delivery and availability of exercise programs in Germany for pediatric cancer patients and survivors are unknown. A national survey analyzed restrictions, challenges and novel approaches of exercise program delivery and scientific research. Method: A two-stage online survey was distributed to providers of exercise programs (acute clinics, non-clinical institutions, rehabilitation facilities) via the established Network ActiveOncoKids. Data was collected during the pandemic in 2022 and 2023 using a combination of open and closed questions. Results: In total, n = 27 (response rate: 82%) and n = 17 (response rate: 63%) providers participated in the first and second survey, respectively. Findings pointed out restrictions in 85% of all exercise programs in 2020 and 2021, with slight reductions in 2022. During pandemic, restrictions with major impact arose within exercise offers during follow-up and declined gradually. Whereas restrictions within the setting of acute therapy had medium or minor impact but persisted beyond. Delivery of provided exercise programs necessitated adaptions, including digital methods, supervised interventions from a distance and change of locations. Discussion: The findings highlight the adaptability, the demand and the potential of exercise programs in pediatric oncology. We assume that exercise professionals have used the pandemic-related challenges to review and modify existing concepts and made adaptations according to local conditions and novel tools for the provision of exercise programs. Nevertheless, a conspicuous lack of exerciserelated care has become evident in certain patients and survivors. Further expansion of programs is imperative to address and accommodate all pertinent needs.